Cystatine C role in predicting the in-hospital adverse outcomes of coronary artery bypass graft surgery - K. S. Shafranskaya; V. V. Kashtalap; A. A. Kuzmina; O. V. Gruzdeva; A. M. Grigoriev; A. N. Sumin; O. L. Barbarash; L. S. Barbarash (Российский кардиологический журнал, 2013)
Aim. To assess the clinical value of cystatin C for the prediction of the in-hospital complication risk among patients with coronary heart disease (CHD) who underwent coronary artery bypass graft surgery (CABG). Material and methods. The perioperative period data were analysed for 583 patients who underwent CABG in March-November 2011. Before the surgery, all patients underwent colour duplex ultrasound of peripheral arteries. One day before CABG and at Day 7 after the surgery, serum levels of creatinine and glomerular filtration rate (GFR; MDRD formula) were assessed. In 150 participants, cystatin C concentration was measured one day before the surgery and at Day 7 after CABG. The incidence of in-hospital adverse outcomes of CABG, such as myocardial infarction, stroke, acute renal failure, and repeat mediastinotomy, was evaluated. In all participants, the risk levels by the EuroSCORE scale were measured. Results. Pre- and post-surgery levels of serum creatinine and GFR did not differ significantly between the low, intermediate, and high EuroSCORE risk groups. Moreover, pre- and post-CABG levels of serum creatinine and GFR were similar in patients with favourable and adverse outcomes. However, the concentration of cystatin C, both before and after CABG, was significantly higher in patients with adverse outcomes, compared to participants with favourable outcomes. Conclusion. These findings suggest that cystatin C could be used as a universal prognostic marker of cardiovascular complications and renal dysfunction in post-CABG patients.